PERANAN KOMPUTER SEBAGAI MEDIA PEMBELAJARAN BAGI ANAK - Pujiriyanto Pujiriyanto (Fakultas Ilmu Pendidikan UNY, 2009)
There is a missconception that computer would make the children being isolate. but in fact computer is usefull to teach social skill to the children. Physically a classroom without access to computer as a potential learning resources result in all isolation environment. Consequently it is very important for the children familiar with computer earlier as an instructional media. Children should be taught about computer advantage in order to improve children learning capability and self confident. There is no doubt where the children interest to computer games and television programs. This condition should be catched sight of as learning modality. By providing educate computer programs to the children will emerge a powerful! As learning media. Children not only become skilled at computer technical skill but understanding the use of computer WI a learning tool. contrasting to entenainment tool. The finest way to dig up most favorable optimum computer advantage it is strongly need fo parent and teacher is proficient with best educate computer program. Teacher must be competence to integrate use of computer as learning and focus in high order thingking skill.Keyword: Computer. children. media